Chemical evolution in high-mass star-forming regions - Fontani, Francesco; Beltrán, Maria Teresa; Vasyunin, Anton (Frontiers in Astronomy and Space Sciences, 2025)
Growing evidence shows that most stars in the Milky Way, including our Sun, are born in high-mass star-forming regions, but due to both observational and theoretical challenges, our understanding of their chemical evolution is much less clear than that of their low-mass counterparts. Thanks to the capabilities of new generation telescopes and computers, a growing amount of observational and theoretical results have been recently obtained, which have important implications not only for our understanding of the (still mysterious) formation process of high-mass stars, but also for the chemistry that the primordial Solar System might have inherited from its birth environment. In this review, we summarise the main observational and theoretical results achieved in the last decades in the study of chemistry evolution in high-mass star-forming regions, and in the identification of chemical evolutionary indicators. Emphasis is especially given to observational studies, for which most of the work has been carried out so far. A comparison with the chemical evolution occurring in other astrophysical environments, in particular in low-mass star-forming cores and extragalactic cores, is also briefly presented. Current open questions and future perspectives are also discussed.